Perlindungan dan Penegakan Hukum Terhadap Anak Selaku Pelaku Tindak Pidana dalam Hukum Positif di Indonesia - Hidayat, Alip Asya (CV WAHANA PUBLIKASI, 2023)
Positive law in Indonesia has recognized the importance of child protection, both as citizens and minors. However, in practice there are still conflicts regarding the balance between law enforcement and the protection of children's rights. Therefore, the purpose of this study is to understand and analyze the effect of positive law on children as innocent victims in Indonesian law. The research method used is normative qualitative research with a focus on legislation. The research findings show that (a) the protection and enforcement of child protection law in Indonesia is specifically outlined in the Child Criminal Justice System (SPPA) (Law Number 11 of 2012). In terms of child punishment, diversion and restorative justice are important alternatives in resolving children's cases; (b) children who commit criminal offenses are still subject to sanctions even with special considerations, in accordance with the provisions of Law Number 3 of 1997 and the SPPA Law. The sanctions can be in the form of actions or criminal sanctions, with an emphasis on rehabilitation and education.